Life Cycle Environmental Impacts of Electricity from Biogas Produced by Anaerobic Digestion - Fusi, Alessandra; Bacenetti, Jacopo; Fiala, Marco; Azapagic, Adisa (Frontiers in Bioengineering and Biotechnology, 2016)
The aim of this study was to evaluate life cycle environmental impacts associated with the generation of electricity from biogas produced by the anaerobic digestion of agricultural products and waste. Five real plants in Italy were considered, using maize silage, slurry and tomato waste as feedstocks and co-generating electricity and heat; the latter is not utilized. The results suggest that maize silage and the operation of anaerobic digesters, including open storage of digestate, are the main contributors to the impacts of biogas electricity. The system which uses animal slurry is the best option, except for the marine and terrestrial eco-toxicity. The results also suggest that it is environmentally better to have smaller plants using slurry and waste rather than bigger installations which require maize silage to operate efficiently. Electricity from biogas is environmentally more sustainable than grid electricity for seven out of 11 impacts considered. However, in comparison with natural gas, biogas electricity is worse for seven out of 11 impacts. It also has mostly higher impacts than other renewables, with a few exceptions, notably solar photovoltaics. Thus, for the AD systems and mesophilic operating conditions considered in this study, biogas electricity can help reduce greenhouse gas (GHG) emissions relative to a fossil-intensive electricity mix; however, some other impacts increase. If mitigation of climate change is the main aim, other renewables have a greater potential to reduce GHG emissions. If, in addition to this, other impacts are considered, then hydro, wind and geothermal power are better alternatives to biogas electricity. However, utilization of heat would improve significantly its environmental sustainability, particularly global warming potential, summer smog and the depletion of abiotic resources and the ozone layer. Further improvements can be achieved by banning open digestate storage to prevent methane emissions and regulating digestate spreading onto land to minimize emissions of ammonia and related environmental impacts.